2017
DOI: 10.18632/oncotarget.19392
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A5 suppresses cyclooxygenase-2 expression by downregulating the protein kinase C-ζ-nuclear factor-κB signaling pathway in prostate cancer cells

Abstract: Annexin A5 (ANXA5) is a member of the annexin protein family. Previous studies have shown that ANXA5 is involved in anti-inflammation and cell death. However, the detailed mechanism of the role of ANXA5 in cancer cells is not well understood. In this study, we investigated the inhibitory effect of ANXA5 on cyclooxygenase-2 (COX-2) in prostate cancer cells. Expression of COX-2 induced by TNF-α was inhibited by overexpression of ANXA5 and inhibition of COX-2 expression by auranofin, which could induce ANXA5 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Contrarily, large amounts of research demonstrated ANXA5 acts as tumor suppressor. For instance, ANXA5 can suppress cell proliferation and metastasis in uterine cervical carcinoma ( 13 ); it transfers to the mitochondria, suppressing the voltage-dependent anion channel (VDAC) oligomerization which leads to prostate cancer cell apoptosis ( 14 ). ANXA5 suppresses murine neuroblastoma cell proliferation by blotting PS which results in the enhanced T cell-dependent tumor immunity ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, large amounts of research demonstrated ANXA5 acts as tumor suppressor. For instance, ANXA5 can suppress cell proliferation and metastasis in uterine cervical carcinoma ( 13 ); it transfers to the mitochondria, suppressing the voltage-dependent anion channel (VDAC) oligomerization which leads to prostate cancer cell apoptosis ( 14 ). ANXA5 suppresses murine neuroblastoma cell proliferation by blotting PS which results in the enhanced T cell-dependent tumor immunity ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Knock-out of the prostate apoptosis response 4 ( Par4 ), a pro-apoptotic tumor suppressor gene, results in spontaneous development of prostate cancer in mice, possibly due to loss of negative regulation of the atypical PKCζ and elevated expression of the anti-apoptotic protein XIAP [ 122 ]. Also, inhibition of PKCζ expression by Annexin A5 seems important in repressing COX-2 expression in prostate cancer cells [ 123 ]. This is in line with several observations showing that elevated expression and alternative splicing of PKCζ promotes an aggressive prostate cancer phenotype [ 124 , 125 ].…”
Section: Nf-κb Signaling Pathways In Prostate Cancersmentioning
confidence: 99%
“…The effect of PKC on the cell cycle is highly context-dependent and varies depending on the specific isoenzyme involved and other factors, such as the time and duration of enzyme activation [ 122 ]. Some studies suggested that PKC-α, PKC-ε [ 124 ], and the atypical PKCs (aPKCs), PKC-λ/ι [ 125 ] and PKC- ζ [ 124 , 126 ], preferably induce cell proliferation and survival, while PKC-δ regulates apoptosis [ 127 ].…”
Section: Pks and Pc Progressionmentioning
confidence: 99%